As Burning Leaves - Jesiolowski, Gabriel (Book collections on Project MUSE., 2017)
"As Burning Leaves offers spaciousness and breath. Both homesick and sick of home, it chronicles a landscape of longing scored with traces of film, contemporary art, and song. Vivid and vital, Jesiolowski's queer insight lends a critical voice to the fleeting: 'wind moves the leaves across the water / they do not gather / do not cling.' A brave and elegant debut"--